Assessment of climate change impacts on water yield in Pahang River Basin - Yusrah Atikah, Ismail (2017)
Climate change also called global warming, refers to the rise in average surface temperatures on Earth. The study main objective were assessing the climate change impacts on water yield in Pahang River Basin. To achieve the study main objective, the specific study were performed as follows; analyse the water-yield, and the impacts of climate change on water yield in Pahang River Basin. The water-yield estimated with simple water-balance analysis, which is rainfall as input and actual evapotranspiration as output. In this study, monthly rainfall derived from the Tropical Rainfall Measuring Mission Multi-satellite Precipitation Analysis (TMPA) satellite image obtained from public domain, meanwhile the actual evapotranspiration estimated using satellite-based biophysical index (i.e. Normalized Difference Vegetation Indices (NDVI)). Analysis for year 2015 and 2016 affected by El Nino, shows rainfall is decreasing compare to typically receive by the region. Therefore produce less water-yield. Meanwhile for 2011 affected by La Nina, shows rainfall is increasing, hence water-yield increase. The results of this study shows climate change give significant impact to the basin water-yield. Thus to maintain water resources, the authorities need to build appropriate reservoirs which the water could be use during droughts.